Telocytes in human liver fibrosis. Issue 3 (8th February 2015) - Fu, Siyi; Wang, Fei; Cao, Yan; Huang, Qi; Xiao, Junjie; Yang, Changqing; Popescu, Laurentiu M.
Abstract Liver fibrosis is a wound‐healing response which engages a variety of cell types to encapsulate injury. Telocyte (TC), a novel type of interstitial cell, has been identified in a variety of tissues and organs including liver. TCs have been reported to be reduced in fibrotic areas after myocardial infarction, human interstitial wall's fibrotic remodelling caused either by ulcerative colitis or Crohn's disease, and skin of systemic sclerosis. However, the role of TCs in human liver fibrosis remains unclear. Liver samples from human liver biopsy were collected. All samples were stained with Masson's trichrome to determine fibrosis. TCs were identified by several immunofluorescence stainings including double labelling for CD34 and c‐kit/CD117, or vimentin, or PDGF Receptor‐α, or β. We found that hepatic TCs were significantly decreased by 27%–60% in human liver fibrosis, suggesting that loss of TCs might lead to the altered organization of extracellular matrix and loss the control of fibroblast/myofibroblast activity and favour the genesis of fibrosis. Adding TCs might help to develop effective and targeted antifibrotic therapies for human liver fibrosis.